Marriage as a Connector: A Conversation about Spatial and Temporal Scales of Partnership and Self-accomplishment in Kenya and Uganda - (:unkn) unknown (My University, 2021)
East African families are heterogeneous institutions, fluid and in transformation. The region is home to a range of competing and sometimes contradictory value systems, with a variety of ethics, codes and practices regarding such matters as marriage, divorce and bridewealth. The intertwining of multiple value systems, together with demographic shifts, intermarriages, dynamics of internal and international migration and new professional avenues have a fundamental bearing on expanding the array of family configurations.The spread of informal unions can in part be understood as a response to economic changes initiated by the structural adjustment programs of the 1980s, and a limited ability to meet the social prerequisites of legitimate family-making, like wedding and marriage costs and the payment of bridewealth, i.e. the transfer of wealth from the groom’s to the bride’s kin. However, individuals and couples of all generations actively re-imagine the future of marriage beyond bridewealth, increasingly questioning the meaning, role and validity of marriage payments, wedding requirements and separations.Changing family constellations and new interpretations of non conventional family-making, where marriage is not officially sanctioned, cohabitation is not an option, or patrilinear ties are less important than matrilateral, may pave alternative pathways for achieving upward social mobility, especially in the context of mobility and migration through kinship networks. In this chapter we wish to address the diversity of marriage in East Africa from a local and gendered perspective. After a quantitative overview on marriage in Kenya and Uganda, we will be focusing on marriage ceremonies, the meaning of divorce for social status and self-accomplishment and finally, the role of mobility in making and unmaking marriage.
Keywords: African Research